The removal of bisphenol a in water treatment plant using ultrafiltration membrane system - Muhamad, M. S. (Springer International Publishing, 2016)
Bisphenol A (BPA) is one of the recalcitrant contaminants that are detected in drinking water sources, as the conventional water treatment plant is incapable of removing it completely. This study was conducted to explore the performance of ultrafiltration (UF) membrane system for the BPA removal in which BPA was spiked in water sample collected from a treatment plant. The effects of process conditions that may influence the removal and flux performance of the membrane including operating pressure, feed pH and BPA concentration, and backwash cleaning were investigated. The results showed that an applied pressure of 1 bar was the optimum pressure for achieving good balance of BPA removal (95 %) and water flux (109 L m−2 h−1) compared to operating pressure of 0.5 and 1.5 bar. The variation of feed pH showed significant impact on BPA elimination with the highest rejection (90 %) achieved at pH 7 while the lowest removal (20 %) at pH 10. BPA concentration had no significant impact on BPA removal as high removal rate (>95 %) was observed regardless of feed concentration (between 10 and 100 μg L−1). The normalized flux showed decreasing trend with filtration cycle due to increased membrane resistance of BPA adsorption onto the membrane. The membrane cleaning via backwash was able to recover 90 % BPA removal even after three consecutive cycles of filtration. This indicated the promising performance of UF membrane system for industrial water treatment.